Novel Cartilage‐derived Biomimetic Scaffold for Human Nucleus Pulposus Regeneration: a Promising Therapeutic Strategy for Symptomatic Degenerative Disc Diseases. Issue 1 (18th February 2013) - Yang, Qiang; Zhao, Yan‐hong; Xia, Qun; Xu, Bao‐shan; Ma, Xin‐long; Liu, Yue; Hu, Yong‐cheng; Li, Hong‐fa; Miao, Jun; Wang, Tao; Ma, Jian‐xiong; Sun, Xiao‐lei
Abstract : Because current therapies have not always been successful and effective, the possibility of regenerating the nucleus pulposus (NP) through a tissue‐engineered construct offers a novel therapeutic possibility for symptomatic degenerative disc diseases (DDDs). However, more research is necessary to identify the optimal scaffold, cell type and mixture of signal factors needed for NP regeneration. Numerous possible scaffolds for NP regeneration have been investigated; they have many shortcomings in common. Various biological scaffolds derived from decellularized tissue and organs have been successfully used in tissue engineering and received approval for use in humans. Regretfully, harvesting of human NP is difficult and only small amounts can be obtained. The macromolecules of cartilage, which include collagen and proteoglycan aggrecan, are similar to those of the extracellular matrix of immature NP. Recent studies have shown that adipose‐derived stem cells (ADSC) can be induced to develop NP‐like phenotypes when stimulated by appropriate signals. We thus reasonably postulated that an ideal NP scaffold for tissue engineering could be fabricated from decellularized cartilage matrix (DCM). Furthermore, a combination of ADSCs and DCM‐derived biomimetic scaffolds would be advantageous in NP tissue engineering and, in the long run, could become an effective treatment option for symptomatic DDD.